The relationship between salivary flow rate and masticatory performance in hypertensive and nonhypertensive complete denture wearers - Anggun Ratu Hutauruk; Ismet Nasution; Ariyani (Indonesia Prosthodontic Association, 2026)
Edentulism is the complete loss of natural teeth, leading patients to rely on complete dentures to restore masticatory function. The success of denture use is influenced by salivary flow rate, which affects retention and stability. Salivary flow may be altered by systemic conditions such as hypertension, potentially reducing masticatory performance. This study aimed to determine the mean salivary flow rate and masticatory performance, and to analyze their relationship in hypertensive and nonhypertensive complete denture wearers at the Dental and Oral Hospital of Universitas Sumatera Utara. This analytic cross-sectional study involved 20 subjects (10 hypertensive and 10 non-hypertensive). Salivary flow rate was measured using the spitting method with sugar-free chewing gum, while masticatory performance was assessed using color-changeable chewing gum and the Visual Analog Scale (VAS). Data were analyzed using Spearman’s correlation test (p<0.05). The mean salivary flow rate was 0.36±0.11 ml/min in hypertensive patients and 0.86±0.15 ml/min in nonhypertensive patients. The mean masticatory performance scores were 2.8±0.78 and 3.9±0.99, respectively. A significant correlation was found between salivary flow rate and masticatory performance in both hypertensive (p=0.0001) and nonhypertensive groups (p=0.001).Keywords: complete denture, hypertensive, salivary flow rate, masticatory performance